2018
DOI: 10.1371/journal.pntd.0006875
|View full text |Cite
|
Sign up to set email alerts
|

The in vivo and in vitro roles of Trypanosoma cruzi Rad51 in the repair of DNA double strand breaks and oxidative lesions

Abstract: In Trypanosoma cruzi, the etiologic agent of Chagas disease, Rad51 (TcRad51) is a central enzyme for homologous recombination. Here we describe the different roles of TcRad51 in DNA repair. Epimastigotes of T. cruzi overexpressing TcRAD51 presented abundant TcRad51-labeled foci before gamma irradiation treatment, and a faster growth recovery when compared to single-knockout epimastigotes for RAD51. Overexpression of RAD51 also promoted increased resistance against hydrogen peroxide treatment, while the single-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 53 publications
3
19
0
Order By: Relevance
“…Sánchez-Valdéz et al (2018) hypothesized that homologous recombination is the cause for dormancy in T. cruzi. It is well-known that the recombination pivot is TcRad51, a protein responsible for the repair of DSBs-either induced by high levels of gamma radiation, or caused by other genotoxic agents that lead to transcriptional and replicational fork arrest (Regis-da-Silva et al, 2006;Gomes Passos Silva et al, 2018). We then observed the effect of gamma radiation in inducing arrest in T. cruzi epimastigotes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Sánchez-Valdéz et al (2018) hypothesized that homologous recombination is the cause for dormancy in T. cruzi. It is well-known that the recombination pivot is TcRad51, a protein responsible for the repair of DSBs-either induced by high levels of gamma radiation, or caused by other genotoxic agents that lead to transcriptional and replicational fork arrest (Regis-da-Silva et al, 2006;Gomes Passos Silva et al, 2018). We then observed the effect of gamma radiation in inducing arrest in T. cruzi epimastigotes.…”
Section: Discussionmentioning
confidence: 99%
“…Gamma radiation generates DSBs in DNA, which are repaired by homologous recombination in T. cruzi. We have previously shown that epimastigotes exposed to 500 Gy of gamma radiation enter in a cell cycle arrest for 4 days, by the end of which are able to resume their cellular growth (Gomes Passos Silva et al, 2018). In order to analyze in detail how gamma radiation affects epimastigotes of T. cruzi from CL Brener strain, we irradiated cells with 500 Gy of gamma rays and labeled them immediately with CFSE.…”
Section: Homologous Recombination Induces Dormancy In T Cruzi Epimasmentioning
confidence: 99%
See 2 more Smart Citations
“…The persistence of RPA foci in the 1 HR rad50 cells is further evidence of defective repair in these cells, explained by RPA remaining associated with ssDNA at sites of damage. This observation may also reflect a damage tolerance strategy employed by T. brucei 22 , but in these circumstances γH2A and RAD51 are not recruited to the break after replication, unlike what is seen in T. cruzi where ionizing radiation tolerance is dependent on RAD51 67 . DNA resection following a DSB is one of the early steps in the DDR.…”
Section: Discussionmentioning
confidence: 91%